Improved physical properties of the quadruple sub-system with the eclipsing binary QZ Carinae - Mayer, P.; Harmanec, P.; Zasche, P.; Catalan-Hurtado, R.; Barlow, B. N.; Fremat, Y.; Wolf, M.; Drechsel, Horst; Chini, R.; Nasseri, A.; Christie, G. W.; Walker, W. S. G.; et al. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
Using a collection of 79 spectra of the quadruple system QZ Car, we were able - for the first time in the optical region - to measure radial velocities of both components of the eclipsing subsystem Ac, and in combination with the photometric solution to obtain masses and radii of both bodies. We confirm that the Ac binary is a semi-detached system with a brighter primary Ac1 and a more massive secondary Ac2. Variations due to the light-time effect and secular changes in the systemic velocities of both binaries, Aa and Ac, allowed us to estimate the period of mutual orbit of binaries Aa and Ac to be about 11700 d. Preliminary improved basic properties of the system and its components are provided.
CRIS-Team WoS Importer:2020-04-21